A Comprehensive Study of the Discovery Potential of NOνA, T2K, and T2HK Experiments. (29th February 2016) - Soumya, C.; Deepthi, K. N.; Mohanta, R.
Abstract : With the recent measurement of reactor mixing angleθ 13 the knowledge of neutrino oscillation parameters has improved significantly except the CP violating phaseδ C P, mass hierarchy, and the octant of the atmospheric mixing angleθ 23 . Many dedicated experiments are proposed to determine these parameters which may take at least 10 years from now to become operational. It is therefore very crucial to use the results from the existing experiments to see whether we can get even partial answers to these questions. In this paper we study the discovery potential of the ongoing NOν A and T2K experiments as well as the forthcoming T2HK experiment in addressing these questions. In particular, we evaluate the sensitivity of NOν A to determine neutrino mass hierarchy, octant degeneracy, andδ C P after running for its scheduled period of 3 years in neutrino mode and 3 years in antineutrino mode. We then extend the analysis to understand the discovery potential if the experiments will run for (5 ν + 5 ν ¯ ) years and (7 ν + 3 ν ¯ ) years. We also show how the sensitivity improves when we combine the data from NOν A, T2K, and T2HK experiments with different combinations of run period. The CP violation sensitivity is marginal for T2K and NOν A experiments even for ten-year data taking of NOν A. T2HK has a significance above5 σ for a fraction of two-fifths values of theδ C P space. We also find thatδ C P can be determined to be better than 35°, 21°, and 9° for all values ofδ C P for T2K, NOν A, and T2HK respectively.